LOCAL FOOD TRADITIONS AND STAPLE FOOD CONSUMPTION: A STUDY OF NASI ARON IN TOSARI VILLAGE - Alifah Nur Aini Fajrin; Muhamad Gunawan Ashari; Novfit Frima Akbar; Roshidan; L. Abdi Zaljalaliwal Ikrom (Magister Ilmu Lingkungan, Fakultas Teknik dan Sains, UPN Veteran Jawa Timur., 2025)
This journal is the result of direct research in the field, the Tengger tribe is an indigenous people who inhabit the highlands around the Bromo mountain area to be precise in Tosari Village, Pasuruan District, East Java Province. The purpose of making this journal is: to be able to find out the origins of the consumption of